Reproductive biology of blue swimming crab, Portunus segnis (Forskal, 1775) in Yumurtalık Cove, Northeastern Mediterranean, Turkey - TURELI, CANAN; YESILYURT, IREM NUR (Mediterranean Marine Science, 2018)
Blue swimming crab, Portunus segnis is a Lessepsian migrant into the Mediterranean and little is known about the biology of it in Iskenderun Bay, Northeastern Mediterranean, Turkey. In the present study the sex ratio, gonadal development stages, gonadosomatic index, size at first sexual maturity, and the fecundity of P. segnis were examined. The specimens of P. segnis were collected monthly from July 2014 to June 2015 (except February) with trawl net from the Yumurtalık Cove. The crabs were found throughout the year and were abundant between July to October (74%). Carapace width range of all samples was between 38.1-163.17 mm, and body weight ranged from 3.46-324.36 g. The population sex ratio was obtained Male:Female=0.7:1 which showed more abundant female population. Fifty percent of the female crabs attained sexual maturity when they reached the sized of 115-119.99 mm CW. The ovigerous female crabs ranging between 101.39- 154.03 mm CW can produced 139379 to 2745236 eggs. The mean fecundity of P. segnis was 1070425±580978 eggs with a mean carapace width of 130.04±12.77 mm. In Yumurtalık Cove, breeding season of P. segnis were observed throughout the year, except winter. Further studies are needed for assessing the reproductive biology of blue crabs in other locations of Turkey.